Rádio universitária na Amazônia paraense: um estudo das rádios Unama FM e rádio Web UFPA - Santos, Izabelly (2019)
The work seeks to study the cultural and educational character of university radio. Reflecting on the space of university radio, as a medium where relevant practical activities can be produced the stages of production of informative content. The research will show how to establish the practice of experimentation, the applicability of the knowledge acquired in journalism and advertising teaching and the additions of citizenship and training in the student universe of the communication area. The objects of study chosen are the Unama FM and Radio WEB UFPA radios, both located in the state of Pará. It will be essential to identify and characterize the different peculiarities inherent to the study objects observed here. It is known that radio is a means of communication accessible to a large part of the population, in ways that this research is directed to these two university radios, which generated the following questions: Even with the potentiality of these radios, is it possible to construct a methodology able to provide better training for these students and professionals who work on the radio? What if, with all the coverage of the radio, and with the programming aimed at the general public (radio listener), could it be possible to educate them with radio mediation, making them more aware and aware of their rights? The research has as general objective to show the role of university radio in the process of training professionals to perform in radio and through this training also demonstrate the importance of their educational role towards regional society. I will use the contributions of Meditsch (2001), which deals with radio in the era of globalization, Gusman (2000), which deals with the particularities of radio, Menezes (2007), which highlights radio and its social space, Freire (1996) and Morin (2002) with the conception of education in the construction of reflexive and critical knowledge, Rincón (2002), who speaks of the listener as a citizen, Herrera Huérfano (1997) with radio and its educational role, Villafaña (1997) (2003) with the role of the student in the production of educational programs, Spenthof (1998) with university radio as a space for experimentation and Walter Benjamin (1986) with the importance of giving voice to the citizen. The method of analysis emphasizes the regional context in which the radio is inserted, and the voices of the subjects who perform and perform their inherent and radio-relevant functions. The study establishes mechanisms capable of ensuring that both the student as well as the professional of the area, show their participatory and active voice within the university radio